“Take Me Home”: Hearing the Voice of Poetic Identity and Language Development in EFL Poetry Writing - Piscayanti, Kadek Sonia; Mujiyanto, Januarius; Yuliasri, Issy; Bharati, Dwi Anggani Linggar (Universitas Negeri Semarang, 2021)
The aim of this research is to explore poetic identity in EFL poetry writing by EFL learners as to know their language development. Poetic identity is the representation of poetry as a language expression that serves as the representation of community sense. EFL learning in this context is the medium to produce the poetry from which the learners learn to invent their identity as to invent their language. This study is a case study with the subjects of study are 29 EFL learners in Universitas Pendidikan Ganesha who wrote poetry writing as their product of learning in poetry course. Each of them wrote 2 poetry which were analyzed based on the poetic identity analysis with Hanauers’ method. From the result of analysis, the voice of poetic identity represents the poets’ voice of self-identity in life (fear, love, and hope) and voice of freedom. This study also illustrates how language is developed to construct meaning and ideas within the mindful and meaningful literacy learning.